Morphological, molecular characterization and pathogenicity of Colletotrichum SPP. isolated from legume crops in Peninsular Malaysia - Mahmodi, Farshid (2013)
The genus Colletotrichum is among the most important groups of plant pathogenic fungi worldwide. The ability to accurately diagnose species is vital for the implementation of effective disease control and quarantine measures. Little is known and published about the population, distribution, biology and genetic diversity of Colletotrichum species on grain legumes in Malaysia for disease management practices. It is clear that Colletotrichum truncatum, Colletotrichum dematium and Colletotrichum gloeosporioides were the main species responsible for the anthracnose on grain legumes in Malaysia. Colletotrichum capsici and C. truncatum are unique species, although it has been suggested that C. capsici is a synonym of C. truncatum. Analysis of molecular data from DNA sequences of multigene loci confirmed the identity and differentiation of these species. The majority species isolated in this research were in match with the classical morphological descriptions in culture, with the exception of partly overlapping morphological characters. Regardless of hostorigination,Colletotrichum isolates exhibited different degrees of variability and overlapping in morphological and cultural characteristics. Colletotrichum truncatum is known to have a broad host range on the Fabaceae family and other crops such as cabbage (Brassica chinensis), pepper (Capsicum annuum), tomato (Solanum lycopersicum), eggplant (Solanum melongena) and lettuce (Lactuca sativa). In contrast, the host range of isolates of C. dematium and C. gloeosporioides is limited to cowpea and soybean, respectively, Centrosema pubescens was also a common host.Colletotrichum truncatum was reported as more prevalent in soybean than other legumes grown in Malaysia. Pathogenic isolates were genetically indistinguishable from non-pathogenic isolates. Pathogenicity data supported variability in C. truncatum structure with diversity in the host. The molecular data showed congruence between genetic diversity and host populations. A clear insight of the genetic diversity and relationship of Colletotrichum spp. isolates has now emerged. The data also revealed high genetic diversity dispersed to the smallest scale, at the regional or field level. No apparent geographic effect was observed. The combined data of six genes comprised of 2771 characters after alignment, of which 985 characters were parsimony informative. Parsimony and neighbor-joining analysis produced similar topology and all Colletotrichum isolates were clustered into 3 welldefined clades with high bootstrap support, representing three distinct species. Histone and GAPDH genes contain the most phylogenetically informative characters among examined taxa, suggesting these loci with high number of polymorphic nucleotide site can be used in phylogenetic studies to build highly resolved phylogenies at the intraspecific level and closely related species. ISSR and RAPD markers used to investigate the genetic composition of Colletotrichum species from legumes were able to differentiate the species examined. Molecular polymorphism assessed by RAPD and ISSR revealed a level of molecular variability greater than that characterized using multigene sequence analysis within and among Colletotrichum species. However, the results between markers were congruent, but the effective marker ratio and subsequent to that the number of private alleles was greater with ISSR markers. The species-specific primer pair sets; CTF 5'-TCCCCTAAAAAGGACGTCTCCCG-3',CTR 5'-TCCCTCCGAATCCCAATGCGAGA-3'; CDF 5'-CCTCGGGACGCCCTCC-3', CDR 5'-CCCAATGCGAGGACGTTA-3' and CGF 5'-CAGCTCCGTCGCCCGGA-3', CGR 5'-TGTTTTACGGCAGGAGTC-3' targeting on ITS-rDNA were designed to use in PCR detection assay for C. truncatum, C. dematium and C. gloeosporioides,respectively. Species specificity of the primers was confirmed by successful detection of Colletotrichum spp. from infected legume plants, and the absence of DNA amplified products from other Colletotrichum species and divergent genus of the fungi. The results of sexual compatibility tests and genetical analysis showed the heterothallic nature of Glomerella truncata. In all the compatible crosses, perithecia, asci and ascospore morphologies were similar to those described earlier. However, the sexual reproduction in C. truncatum has only been observed under laboratory conditions, and has never been reported in the field. The results indicated the intrinsic potential of C.truncatum for sexual reproduction by producing perithecia under natural conditions.